Transformasi Pendidikan dalam Islam: Menjelajahi Filsafat Pendidikan Islam di Era Modern - Haidar M. Alfatih (Yayasan Azzuhri Lengkok Lombok Timur, 2023)
This research aims to explore the transformation of education in Islam with a focus on understanding the philosophy of Islamic education in the modern era. Islamic education has a long, rich and deep history, and has undergone various transformations over time. The modern era brought significant changes in the way Islamic education is viewed and practiced. This research uses literature analysis and historical tracing methods to explore the roots of traditional Islamic educational philosophy and understand how this philosophy has adapted to the challenges and changes faced in the modern era. We also examine how educational transformations in Islam may influence future Islamic educational thinking and practice. The research results show that education in Islam has experienced a significant transformation in terms of methodology, curriculum and learning approaches. Traditional Islamic educational philosophy, which has its roots in the Koran and Hadith, has been integrated with modern educational principles such as inclusive education, information technology, and competency-based education. This reflects efforts to maintain the relevance of Islamic education in facing the challenges and opportunities of the modern era. This research provides deeper insight into how education in Islam has changed and developed over time, while maintaining the religion's core values. This study also has practical implications in designing Islamic education programs that suit the demands of the times, so that they can provide greater benefits for Muslim communities in the modern era. Keywords: educational transformation, educational philosophy, modern